2020
DOI: 10.2147/ppa.s251993
|View full text |Cite
|
Sign up to set email alerts
|

<p>Attitude Towards Drug Therapy in a Community Mental Health Center Evaluated by the Drug Attitude Inventory</p>

Abstract: Introduction: Negative attitude towards drug therapy can foster limited adherence to treatment, which remains one of the biggest obstacles for implementing effective treatments, especially long term. Purposes: The purposes of the study were 1) to evaluate the attitude towards drug therapy among a representative sample of patients treated in a community psychiatric service using 30-item Drug Attitude Inventory (DAI-30); 2) to evaluate the DAI-30 dimensions, applying factorial analysis; and 3) to highlight the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(94 reference statements)
1
6
1
Order By: Relevance
“… 78 , 79 This result is in line with the correlations we found between some variables and specific areas of WHOQOL-BREF, indicating that good medical, relational and social conditions can favourably condition QOL and in turn conditioned attitude towards therapy. 80 The good value of Cronbach’s alpha confirms the reliability of WHOQOL-BREF scale for measuring quality of life also studies in a naturalistic setting, as observed by some authors. 79 …”
Section: Discussionsupporting
confidence: 76%
“… 78 , 79 This result is in line with the correlations we found between some variables and specific areas of WHOQOL-BREF, indicating that good medical, relational and social conditions can favourably condition QOL and in turn conditioned attitude towards therapy. 80 The good value of Cronbach’s alpha confirms the reliability of WHOQOL-BREF scale for measuring quality of life also studies in a naturalistic setting, as observed by some authors. 79 …”
Section: Discussionsupporting
confidence: 76%
“…39,43 Other studies highlighted that being married can be a protective factor for many psychiatric disorders, favoring a positive attitude towards therapy. 44,45 In the present study, the mental wellbeing levels of participants who had a bachelor's degree were found to be lower than those at other education levels. In some studies examining mental health in terms of education level, it was reported that those with a medium education level 39 and those with a low education level experience more mental health problems.…”
Section: Discussioncontrasting
confidence: 54%
“…To investigate attitudes toward therapy, further studies with validated questionnaires, such as the 30-item Drug Attitude Inventory, are needed. 32 Second, because our study was a cross-sectional study, this study could not elucidate the causal relationships between the predictors and the perception of the difficulty of BDZ dose reduction. Third, our participants were limited to those receiving long-term BDZ treatment.…”
Section: Discussionmentioning
confidence: 95%